Black Justice, White Fear: when Reparations are framed as Genocide - Mickens, Jasmine (Self-Published on 𝘚𝘶𝘣𝘵𝘳𝘢𝘤𝘬, 2025)
This month, in an unprecedented move in U.S. refugee policy, the United States granted refugee status to Afrikaners on the grounds that the white minority in South Africa is facing racial persecution—even genocide. American officials welcomed the first wave of at least 49—citing claims that they are, “being brutally killed,” and “their land confiscated.” This narrative is unsubstantiated, historically dishonest, and morally corrosive. Let’s be clear: There is no campaign of extermination against Afrikaners. There are no mass land seizures. There is no humanitarian crisis. What exists is a shared vulnerability to crime that affects both Black and White rural South African farmers—driven by geography, poverty, and policing gaps, not race. There is unfinished business of South Africa’s democratic transition that left land reform untouched. The South African government finally seeks to correct what colonial conquest and apartheid codified: the violent dispossession of land that engineered Black landlessness into a permanent system of poverty and racial capitalism. There is a growing, global discomfort among formerly unassailable white communities whose inherited privileges are finally—symbolically more than materially—being named, questioned, and historicized. And there is a symbolic shift among conscious African youth—moving the ideological center of gravity toward justice, repair, and Black political self-determination. That shift alone has proven intolerable to some.
Keywords: Racial justice; White supremacy; Anti-Black Racism; Social fear; Systemic inequality; Black resistance; Media narratives; Historical injustice; Public perception; Legal discourse